The analysis, design and development of a social studies instructional package for a primary school - Sim, Hwee Hwang. (2008)
The focus of this dissertation is the creation of an instructional package, which is based on the new Ministry of Education Social Studies syllabus, for the Primary 4 Social Studies teachers of the XYZ school. The purpose is to help the teachers overcome the obstacle of insufficient resources for effective teaching.